Sodium 2-iodobenzenesulfonate monohydrate - Arshad, Muhammad Nadeem (International Union of Crystallography, 2008)
In the title compound, Na(+)·C(6)H(4)IO(3)S(−)·H(2)O, the Na atom is hexacoordinated by O atoms, forming a two-dimensional sheet-like structure in the bc plane, with the iodobenzene rings protruding above and below. Na⋯O contact distances are in the range 2.419 (2)–2.7218 (18) Å and O⋯Na⋯O angles are in the range 73.70 (5)–158.64 (7)°. The crystal structure is stabilized by O—H⋯O and C—H⋯O hydrogen bonds and C—H⋯π interactions. The I atom is disordered over two positions with occupancies of 0.78 (2) and 0.22 (2).